Optical Coherence Tomography in the Diagnosis of Open-angle Glaucoma - Yu. N. Yusef; E. E. Kazaryan (Oftalʹmologiâ, 2024)
This literature review provides information on the capabilities and role of OCT-A in the diagnosis of open-angle glaucoma. The need for non-invasive methods of assessing the ocular vasculature has led to the development of OCT-angiography (OCT-A), which provides information on the state of both the retinal structure and its vascular bed through blood flow analysis, further increasing the value of this imaging method compared to conventional OCT. Blood flow assessment with OCT-A can be used to detect many retinal vascular abnormalities, such as the definition of areas of non-perfusion, non-functioning vessels, the appearance of new vessels in areas that are avascular, increased vascularity, the presence of micro- and macroaneurysms, capillary remodeling, macular telangiectasia, and venous malformations. OCT-A is a non-invasive imaging tool for the retinal and choroidal vasculature, providing a unique view of the vascular system that can be combined with information from other imaging modalities to complement and eventually provide unique information to assist the eye care practitioner in diagnosing or evaluating the effectiveness of interventions. OCT-A parameters are measured in the peripapillary region, and monitoring peripapillary and macular vessel density can provide important information to assess glaucoma progression and predict the rate of disease worsening. Studies show a strong correlation between OCT parameters, OCT parameters, and visual function as measured by visual field analysis in glaucomatous eyes. Future prospects for OCT-A in glaucoma diagnostics using artificial intelligence to predict structural and functional features based on early vascular changes will provide opportunities for early identification of patients at high risk for developing and rapidly progressing glaucoma. OCT-A has the potential to become part of glaucoma diagnostics and treatment.